السلطة التنظيمية للسلطات الادارية المستقلة-دراسة مقارنة (الجزائر، فرنسا) - عبد الرؤوف خمري; صبري معوش (My University, 2024)
Study summary The Algerian legislator granted the independent administrative authorities several powers to exercise their authority, which is represented by the power of control, and one of the most important powers that the legislator granted them legally is the regulatory jurisdiction that the valid constitution granted the executive authority. This is what raised the issue of the constitutionality of the regulatory jurisdiction of the independent administrative authorities. This is what prompted the Council of State The French should intervene to clarify the constitutionality of this authority, especially since this jurisdiction is legally recognized. ............................... ملخص الدراسة منح المشرع الجزائري للسلطات الإدارية المستقلة عدة صلاحيات لممارسة سلطتهاوالتي تتمثل في سلطة الضبط، ومن أهم الاختصاصات التي منحها إياها المشرعبصفة قانونيةالاختصاص التنظيمي الذي خوله الدستور الصالح السلطة التنفيذية، هذا ما أثارمسألة دستورية الاختصاص التنظيمي للسلطات الإدارية المستقلة، هذا ما دفعبمجلس الدولة الفرنسيأن يتدخل لتوضيح دستورية هذه السلطة خاصة وأن هذاالاختصاص معترف به قانونيا. .......................... Résumer Le législateur algérien a accordé aux autorités administratives indépendantes plusieurs pouvoirs pour exercer leur autorité, qui est représentée par le pouvoir de contrôle, et l'un des pouvoirs les plus importants que le législateur leur a accordé légalement est la compétence réglementaire que la constitution en vigueur a accordée au pouvoir exécutif. C'est ce qui pose la question de la constitutionnalité de la compétence réglementaire des autorités administratives indépendantes. C'est ce qui a poussé le Conseil d'État à intervenir pour clarifier la constitutionnalité de cette autorité, d'autant plus que cette compétence est légalement reconnue.